A CD45‐based barcoding approach to multiplex mass‐cytometry (CyTOF). (2nd February 2015) - Lai, Liyun; Ong, Raymond; Li, Juntao; Albani, Salvatore
Abstract: CyTOF enables the study of the immune system with a complexity, depth, and multidimensionality never achieved before. However, the full potential of using CyTOF can be limited by scarce cell samples. Barcoding strategies developed based on direct labeling of cells using maleimido‐monoamide‐DOTA (m‐DOTA) provide a very useful tool. However, using m‐DOTA has some inherent problems, mainly associated with signal intensity. This may be a source of uncertainty when samples are multiplexed. As an alternative or complementary approach to m‐DOTA, conjugating an antibody, specific for a membrane protein present on most immune cells, with different isotopes could address the issues of stability and signal intensity needed for effective barcoding. We chose for this purpose CD45, and designed experiments to address different types of cultures and the ability to detect extra‐ and intra‐cellular targets. We show here that our approach provides an useful alternative to m‐DOTA in terms of sensitivity, specificity, flexibility, and user‐friendliness. Our manuscript provides details to effectively barcode immune cells, overcoming limitations in current technology and enabling the use of CyTOF with scarce samples (for instance precious clinical samples). © 2015 The Authors. Published by Wiley Periodicals, Inc.